2019
DOI: 10.1002/adma.201903738
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Defect Dependence of Thermal Conductivity in Epitaxial WO3 Thin Films

Abstract: According to the Boltzmann transport theory of phonons, the lattice thermal conductivity (κ L ) depends mainly on structure-related parameters including the specific heat, the velocity, and the scattering of phonons. One common strategy for the manipulation of phonon transport has been to introduce lattice imperfections in materials which alters the mean free path of phonons, particularly for applications in thermoelectric energy conversion. [1] Based on the well-established Abeles theory of interactions betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 38 publications
8
28
0
Order By: Relevance
“…4(b)]. Very similar decreasing tendency is also seen in the κ of WOx epitaxial films grown on LaAlO3, which is reported by Ning et al 21 The κ of WO2.97 was ~7 W m −1 K −1 and it decreased to ~2 W m −1 K −1 with decreasing x to 2.92, then gently decreased with decreasing x (Figs. S3 and S4).…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…4(b)]. Very similar decreasing tendency is also seen in the κ of WOx epitaxial films grown on LaAlO3, which is reported by Ning et al 21 The κ of WO2.97 was ~7 W m −1 K −1 and it decreased to ~2 W m −1 K −1 with decreasing x to 2.92, then gently decreased with decreasing x (Figs. S3 and S4).…”
Section: Resultssupporting
confidence: 82%
“…WOx can be epitaxially grown on perovskite oxide single crystals coherently. [17][18][19][20][21] Therefore, we expected that WOx with 1D tunnel structure can be stabilized on a substrate. In fact, Ning et al 21 reported that the thermal conductivity of WOx films grown on (001) LaAlO3 substrate by modulating the oxygen atmosphere during the growth decreased dramatically with decreasing the x whereas the electrical conductivity increased oppositely.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with polycrystalline oxide films ( e.g ., Co 3 O 4 ), in which the response is slow even with high voltages, epitaxial complex oxides are of greater interest. This arises from two main reasons: The ordered channels present in the crystal lattice allow easier migrations of oxygen or hydrogen ions, and the strong correlations among the lattice, spin, charge and orbitals enable a concomitant control of various properties besides magnetic, for example, optical, electrical, and thermal. , Many strongly correlated oxides exhibit fascinating topotactic phase transitions, ,,, but obtaining reversible control of the magnetic moment above room temperature in such ordered oxides has remained challenging.…”
mentioning
confidence: 99%